Virtual Sprint Outpatient Electronic Health Record Training and Optimization Effect on Provider Burnout - English, Eden F.; Holmstrom, Heather; Kwan, Bethany W.; Suresh, Krithika; Rotholz, Stephen; Lin, Chen-Tan; Sieja, Amber (Applied Clinical Informatics, 2022)
Objectives This study aimed to develop a virtual electronic health record (EHR) training and optimization program and evaluate the impact of the virtual model on provider and staff burnout and electronic health record (EHR) experience.Methods UCHealth created and supported a multidisciplinary EHR optimization and training program, known as the Epic Sprint Program. The Sprint Team conducted dozens of onsite Sprint events over the course of several years prior to the pandemic but transitioned to a fully virtual program and successfully “sprinted” 21 outpatient clinics from May to December 2020. Core program components of group and 1:1 training, workflow analysis, and new or adjusted EHR build were unchanged from the onsite model. Pre- and post-Sprint surveys provided detailed, objective data about EHR usability, EHR proficiency, job satisfaction, and burnout.Results The EHR Net Promoter Score (NPS), a likelihood to recommend metric, increased by 39 points (−3 pre and 36 post; p < 0.001) for providers and 29 points (8 pre and 37 post; p = 0.001) for staff post-Sprint. Positive provider (NPS = +53) and staff (NPS = +47) NPS scores indicated a high likelihood to recommend the Sprint Program. Post-Sprint surveys also reflect an increase in providers (10%; p = 0.04) and staff (9%; 0.13) who indicated “no burnout” or “did not feel burned out.”Discussion The UCHealth Sprint Team transitioned this comprehensive, enterprise level initiative from an onsite model to a fully virtual EHR training and optimization program during the first few months of the novel coronavirus disease (COVID-19) pandemic. Despite this change in program delivery, survey data clearly demonstrated improved EHR satisfaction, a high likelihood to recommend a sprint to a friend or colleague, and a trend toward burnout reduction in providers and staff.Conclusion Changing an existing on-site EHR optimization program to a purely virtual format can be successful, and this study showed improved provider and staff EHR satisfaction with reduced burnout.
Keywords: optimization; virtual EHR training; sprint; virtual training; virtual optimization; strategies for health IT training; clinical informatics; professional training; education; distance; process improvement; system improvement; efficiency improvement; performance improvement